Assessing the Effectiveness of Professional Development Training on Autism and Culturally Responsive Practice for Educators and Practitioners in Ethiopia - Zeleke, Waganesh A.; Hughes, Tammy L.; Kanyongo, Gibbs (Frontiers in Psychiatry, 2021)
This study examines the effect of professional development training on educators' and practitioners' knowledge of Autism and the use of culturally responsive practices. Using a single group, pre-post design, data was gathered from 34 educators and health professionals (i.e., teachers, counselors, psychologists, therapists, therapeutic care workers, social workers, and nurses) in Ethiopia. A week-long training covering ASDs and culturally responsive evidence-based training was provided to participants. Results showed significant improvement in participants' knowledge about ASD symptoms, nature, characteristics, as well as intervention selection. Participants' use of culturally informed approaches, in their area of professional service, showed a high level of participants' knowledge and low-level use of culturally responsive practices, policies, and procedures. Recommendations for addressing cultural factors impacting the diagnosis and treatment-seeking approaches to ASD in Africa are provided.